2014
DOI: 10.1257/app.6.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Keeping It Simple: Financial Literacy and Rules of Thumb

Abstract: Individuals and micro-entrepreneurs often lack su¢ cient …nancial literacy to make the complex …nancial decisions they face. We conduct a randomized control trial with a bank in the Dominican Republic to compare the impact of two distinct …nancial literacy programs. The …rst is a standard, fundamentals-based accounting training. The second is a simpli…ed, rule-of-thumb training that teaches basic heuristics to manage …nances. We …nd that only the latter produced signi…cant improvements in business practices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
425
2
24

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(476 citation statements)
references
References 31 publications
25
425
2
24
Order By: Relevance
“…A decade ago, Hausman (2005) highlighted how much of the existing research had examined product and process innovations and neglected non-technological innovation, such as new management practices. Since then, management and managerial skills have received increased attention as a factor explaining differences in firms' performance in developing countries with evidence spanning various geographical areas (Bloom et al, 2013;Drexler et al, 2014;Karlan and Valdivia, 2011;Mano et al, 2012). Moreover, we found some qualitative and narrative evidence of the benefit of market innovations on firms, mainly in the informal sector (Hall et al, 2012;Ramani et al, 2012).…”
Section: 1mentioning
confidence: 61%
“…A decade ago, Hausman (2005) highlighted how much of the existing research had examined product and process innovations and neglected non-technological innovation, such as new management practices. Since then, management and managerial skills have received increased attention as a factor explaining differences in firms' performance in developing countries with evidence spanning various geographical areas (Bloom et al, 2013;Drexler et al, 2014;Karlan and Valdivia, 2011;Mano et al, 2012). Moreover, we found some qualitative and narrative evidence of the benefit of market innovations on firms, mainly in the informal sector (Hall et al, 2012;Ramani et al, 2012).…”
Section: 1mentioning
confidence: 61%
“…Valdivia (2014) finds positive short-and mid-term effects of business training on revenues and business practice for existing entrepreneurs in Peru. In the Dominican Republic, Drexler, Fischer and Schoar (2010) find that simple rules of thumb increase the likelihood of keeping accounting records, calculating monthly revenues, and separating household and business records. However, more complex training does not affect business practice.…”
Section: Contextmentioning
confidence: 99%
“…A number of papers have noted that the decision to take on expensive debt is correlated with household characteristics such as financial literacy (Lusardi and Mitchell, 2014;Lusardi and Tufano, 2009), cognitive abilities (Agarwal and Mazumder, 2013;Stango and Zinman, 2009), and age (Agarwal et al, 2009). Others have shown that these behaviors can be lessened through disclosure and framing (Bertrand and Morse, 2011;Stango and Zinman, 2011), subsidies (Cole et al, 2011), or simplification (Drexler et al, 2014). Research on the exact choice inefficiencies that contribute to overpayment for debt highlight the willingness to search across credit contracts (Stango and Zinman, 2016;Zinman, 2015).…”
Section: Introductionmentioning
confidence: 99%